434 Correlation of endometrial tumor DNA mismatch repair status and MELF-pattern invasion. (13th November 2020) - DiNobile, C; Kertowidjojo, E; Wen, X; Tornos, C; Gossner, G; Burke, W; Pearl, M
Abstract : Introduction: Endometrial adenocarcinoma is the most common gynecologic malignancy in the United States. Between 10–30% of endometrial adenocarcinomas exhibit microsatellite instability (MSI), a type of genetic hypermutability that results from impaired DNA mismatch repair (MMR). On pathologic review, MSI can be indirectly identified by immunohistochemical (IHC) staining for deficient MMR protein expression. Another component of pathologic review is to assess for microcystic, elongated, and fragmented (MELF) pattern of invasion, characterized by a fibromyxoid stromal reaction and the formation of microcysts. To date, there are no studies assessing the correlation of MMR status and MELF-pattern invasion in endometrial adenocarcinoma. Methods: We performed an IRB-approved, retrospective review of medical records and pathology slides of surgical cases of endometrioid endometrial adenocarcinoma between January 2016 and January 2020. Results: Our results did not demonstrate a correlation between MMR mutation status and the presence of MELF-pattern invasion. The presence of MMR mutation was associated with age, stage of disease, and a history of stroke. The presence of MELF-pattern invasion was not associated with various clinical factors or comorbidities. Conclusions: Our study did not demonstrate a relationship between MMR status and presence of MELF pattern invasion. We also did not re-demonstrate prior findings that MELF-pattern invasion is associated with higher rates of lymph node metastases or lymphovascular space invasion (LVSI). Future directions include investigation into the relationship among MMR and age, stage of disease, and history of stroke, as this could potentially impact treatment planning.